The Effect of Capital Structure, Financial Literacy and Technology Adoption on Financial Reporting Efficiency in the Indonesian Food & Beverage Industry - Thanne, Stevanus; Ariadi, Wa; Rerung, Ahadi (International Journal of Business, Law, and Education, 2024)
This study examines the influence of capital structure, financial literacy, and technology adoption on the efficiency of financial reporting in the Indonesian Food & Beverage (F&B) sector. Using survey questionnaires and data analysis with SPSS version 26, a sample of 150 enterprises from different industrial groups was analyzed. Descriptive statistics, correlation analysis, multiple regression analysis, and mediation analysis were performed to investigate the relationships among the research variables. The findings show important positive connections between levels of financial knowledge, practices of adopting technology, and efficiency in financial reporting. However, metrics related to capital structure did not have a significant impact. Mediation research shows that financial literacy levels partly mediate the connection between technology use and financial reporting efficiency. These results highlight the significance of knowledge and skills of individuals and the technical systems in improving the way financial information is reported in the Indonesian food and beverage industry.